2021
DOI: 10.1111/eip.13205
|View full text |Cite
|
Sign up to set email alerts
|

First episode of psychosis in Guam: The role of ethnicity and neighbourhood factors

Abstract: Objective Ethnicity, neighbourhood ethnic density, and four additional neighbourhood factors (urbanicity, crime, voting, and poverty) were examined in relation to the incidence of first episode of psychosis (FEP) in the Pacific Island of Guam. Methods All first contact patients seen at the Guam Department of Mental Health and Substance Abuse (DMHSA) between January 2005 and December 2007 that met DSM‐IV criteria for the diagnosis of a psychotic disorder were included. At the time of the study, DMHSA was the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Mixed findings were reported for the FEP and FES populations, with Rosenfarb et al [29 ▪ ] noting that urbanicity was not a significant independent predictor of FEP. Another study found that metropolitan areas in the capital city were high-risk zones for incidence of nonaffective FEP, and this was also associated with a higher density of the migrant population [26 ▪ ].…”
Section: Effects Of Urbanization By Type Of Psychosismentioning
confidence: 95%
See 3 more Smart Citations
“…Mixed findings were reported for the FEP and FES populations, with Rosenfarb et al [29 ▪ ] noting that urbanicity was not a significant independent predictor of FEP. Another study found that metropolitan areas in the capital city were high-risk zones for incidence of nonaffective FEP, and this was also associated with a higher density of the migrant population [26 ▪ ].…”
Section: Effects Of Urbanization By Type Of Psychosismentioning
confidence: 95%
“…The most commonly cited definition of an urban area was based on census or administrative data and classification [11 ▪ –14 ▪ ,15,16 ▪▪ ,17,18 ▪ ,19 ▪ ]. Population density [11 ▪ ,13 ▪ ,20 ▪ ,21 ▪ ,22 ▪▪ ,23 ▪ ,24 ▪ ] and population size in a specific area [13 ▪ ,19 ▪ ,25 ▪ –29 ▪ ] were also common parameters used to delineate the urban-rural divide. Other related parameters included settlement size [11 ▪ ] and dwelling density [11 ▪ ,30 ▪ ], percentage of flats and apartments [20 ▪ ,31 ▪▪ ], and the age of such places of dwelling [31 ▪▪ ].…”
Section: Definitions Of Urbanicity/urbanizationmentioning
confidence: 99%
See 2 more Smart Citations